Ethnoknowledge in latin america. Appropriation of genetic resources and bioethics - Herrera Vásquez, Sandra; Rodríguez Yunta, Eduardo (Acta Bioethica, 2004)
In this document we argue the importance of taking into consideration the indigenous traditional knowledge or "ethnoknowledge". The pharmaceutical industries and the biotechnological companies have a great interest in this type of knowledge due to the real possibility of finding, within biodiversity, new active products on health and new genes with properties for food improvement. This knowledge is used without recognizing its origin nor compensating the indigenous population for their help. At this moment, on one hand, laws do not contribute to the protection of this knowledge and, on the other, the possibilities of succeeding in learning how medicinal plants have been historically used by chamanes or machis in Latin American are even further away.